Phase 2 randomized placebo‐controlled study of lasmiditan for the acute treatment of migraine in Japanese patients. Issue 5 (15th May 2021) - Sakai, Fumihiko; Takeshima, Takao; Homma, Gosuke; Tanji, Yuka; Katagiri, Hideaki; Komori, Mika
Abstract: Objective: To evaluate the efficacy and safety of lasmiditan in Japanese adults with migraine. Background: Global clinical studies have demonstrated the efficacy and safety of lasmiditan in the acute treatment of migraine. Methods: This was a multicenter, randomized, double‐blind, placebo‐controlled, phase 2 study in Japan (NCT03962738), which enrolled adults with migraine with or without aura. Participants were randomized 7:3:7:6 to placebo, lasmiditan 50 mg, 100 mg, or 200 mg to be self‐administered orally within 4 h of onset of a single moderate‐to‐severe migraine attack. Participants recorded their response to treatment prior to dosing and for 48 h postdose. The primary endpoint was headache pain freedom at 2 h postdose. Results: Participants ( N = 846) were randomized and treated ( N = 691, safety; N = 682, modified intent‐to‐treat). At 2 h postdose, a significantly higher proportion of participants were headache pain‐free in the lasmiditan 200 mg (40.8%, 73/179; odds ratio 3.46 [95% confidence interval 2.17 to 5.54]; p < 0.001; primary objective) and 100 mg groups (32.4%, 67/207; odds ratio 2.41 [1.51 to 3.83]; p < 0.001) compared with the placebo group (16.6%, 35/211), whereas the lasmiditan 50 mg group had a numerically higher proportion of participants headache pain‐free (23.5%, 20/85; odds ratio 1.55 [0.83 to 2.87]; p = 0.167) compared with placebo. A statistically significant linear dose–response relationship for pain freedom was achieved at 2 h by a Cochran–Armitage trend test ( p < 0.001). Lasmiditan treatment was also associated with headache pain relief, most bothersome symptom freedom, and improvement on disability and Patient Global Impression of Change outcomes. The majority of treatment‐emergent adverse events were mild and of short duration, the most common of which were dizziness (39.4%; 188/477), somnolence (19.3%; 92/477), and malaise (10.5%; 50/477) in all lasmiditan groups, with no serious adverse events reported. Conclusions: Lasmiditan was well tolerated and effective for the acute treatment of Japanese patients with migraine, consistent with global phase 3 studies.